Sumbangan Teologi Penciptaan Kristiani Dalam Ensiklik Laudato-Si Artikel 62-75 Bagi Persoalan Ekologis - Mathias Jebaru Adon; FX Armada Riyanto; Pius Pandor (Sekolah Tinggi Teologi Berita Hidup, 2022)
This study aims to explain the concept of creation theology according to the Catholic Church's view as stated in the Encyclical Laudato-Si articles 62-75. This is motivated by the complexity of ecological problems with various causes. So the solution is not only from one way of interpreting and changing reality. It is also necessary to ask for help from various cultural treasures of the nation, especially religion if you want to develop a complete ecology. In this regard, the Catholic Church as a religious institution is very open to dialogue with philosophical thought and the scientific sciences, and this has enabled the Church to produce various syntheses between faith and reason. This research uses the method of literature study and critical reading of the creation story in the Book of Genesis. This research finds that the Catholic Church based on the Bible from the beginning has a solid view of the concept of creation that humans are called to care for and preserve the created nature. Pope Francis emphasized this in his encyclical Laudato-Si articles 62-75. Therefore, the task of caring for the created world is the call and duty of the Christian faith. By realizing this the complexity of environmental problems can be overcome.